Thermodynamic and dynamic stability of NaLiC4: Exploring superconductivity in a layered hexagonal compound through first-principles calculations - Pluengphon, Prayoonsak; Sukmas, Wiwittawin; Tsuppayakorn-aek, Prutthipong; Kotmool, Komsilp; Sakulkalavek, Aparporn; Inceesungvorn, Burapat; Bovornratanaraks, Thiti; Luo, Wei (My University, 2024)
The layered hexagonal compound NaLiC4 has been thoroughly investigated to assess its thermodynamic and dynamic stability in comparison to its parent compounds NaC2 and LiC2. Utilizing first-principles calculations and phonon analyzes, NaLiC4 has demonstrated remarkable stability within a pressure range of 10 to 100 GPa, surpassing the thermodynamic stability of NaC2 and LiC2. It exhibits metallic behavior with distinctive electronic bands along high symmetry paths, suggesting a conducive environment for superconductivity. The superconducting transition temperature (Tc) of NaLiC4 under different pressures was estimated using the Allen–Dynes equation, with a maximum Tc of 79 K observed at 10 GPa. However, as pressure increases, Tc gradually decreases, indicating the significant impact of external pressure conditions on the superconducting properties. Notably, the in-plane E2g phonon mode originating from the layered hexagonal structure of carbon atoms plays a crucial role in facilitating electron–phonon coupling and influencing the superconducting behavior and Tc of NaLiC4. These findings highlight the thermodynamic and dynamic stability of NaLiC4 as a promising candidate for exploring superconductivity, offering insights into its electronic properties, pressure-dependent Tc behavior, and the influence of specific phonon modes. Further theoretical investigations and experimental studies are necessary to fully unlock the potential of NaLiC4 and its contribution to the development of high-performance superconductors.
Keywords: Cluster expansion; Eliashberg theory; First-principles calculations; High pressure; Lattice dynamic; Sodium lithium carbide; Superconductivity; Thermodynamic stability